Doing Manual Paraphrasing: What Should the Students Do in Paraphrasing or Rewriting English Writing? - Fitria, Tira Nur (STAIN Sultan Abdurrahman Kepulauan Riau, 2024)
The issue of plagiarism and students' writing difficulties appeared to be a difficulty for teachers, so the existence of paraphrasing is a means to prevent plagiarizing. The objective of this study is to describe manual paraphrasing for students in paraphrasing or rewriting English writing. This research is descriptive qualitative. The analysis shows that manual paraphrasing is the activity of rewriting a text into another form manually without the help of online tools. In teaching paraphrasing manually, ten several strategies can be used by students, including using synonyms, changing the word form, changing active or passive sentences, changing transitions/connectors, changing/rearranging the order of ideas, changing or modifying text structure, simplifying or summarizing sentence, changing the double negative into a positive form, adding quotation marks for important points, and combining paraphrasing techniques. Students need to combine these strategies by applying more than two strategies than a single paraphraseIn manual paraphrasing, students must carefully study the source material, comprehend its meaning, attempt to explain it, and then rewrite it using their words while preserving the same meaning. Manual paraphrasing requires more effort and takes time than using automated tools, but the results may be better than expected.